An entirely fmoc solid phase approach to the synthesis of daptomycin analogs. Issue 1 (16th February 2018) - Barnawi, Ghufran; Noden, Michael; Taylor, Robert; Lohani, Chuda; Beriashvili, David; Palmer, Michael; Taylor, Scott D.
Abstract: Daptomycin is an important Ca 2+ ‐dependent cyclic lipodepsipeptide antibiotic used to treat serious gram‐positive infections. The search for daptomycin analogs with improved activity and their application as tools for studying its mechanism of action has prompted us to develop an entirely Fmoc solid phase approach to the synthesis of daptomycin analogs. Key to the success of this approach was the development of conditions that allowed for the formation of the ester bond on resin‐bound peptides consisting of residues 1‐10 and the decanoyl lipid tail. The esterification reaction proceeded more efficiently on Tentagel resin as opposed to standard polystyrene resin. This approach was used to synthesize a series of analogs in which each position of Dap‐E12‐W13, a relatively active daptomycin analog, was individually substituted by alanine. Only positions 2, 6, and 11 were found to be amenable to substitution by alanine in that the corresponding alanine analogs were only 1.5‐ to 4‐fold less active than Dap‐E12‐W13. We also found that the daptomycin analog, Dap‐K6‐E12‐W13, exhibits in vitro activity approaching that of daptomycin at physiological Ca 2+ concentration. Studies with Dap‐K6‐E12‐W13 and model liposomes indicate that this analog interacts with membranes by the same mechanism as daptomycin. This analog is currently being used as a lead for the development daptomycin analogs with improved activity. Abstract :